(untitled) (Quinto Sol, 2025)
This article investigates the moment when the separation of Church and State became considered feasible in Peru, at the end of Augusto B. Leguía’s authoritarian regime (1919-1930). It examines the strong corporate alliance that existed between the State and the Catholic Church, represented by the president and the Archbishop of Lima, Emilio Lissón, in contrast to the political frictions that had existed in previous years. It also analyzes the criticisms that emerged, which questioned the political-pastoral model developed after the collapse of the government in 1930. This study can contribute to discussions on the importance of changes in Church-State relations, their viability in the context of early 20th-century society, and the critiques of a corporate order of unity as the foundation for secular projects.